Core network evolution planning oriented 5G - Xu YANG; Ziyu XIAO; Yongping SHAO; Xiaoming SONG (Dianxin kexue)
Firstly,the 5G standard and industrial progress were summarized,and the 5G core network architecture,key technologies and interworking architecture were combed.On this basis,the idea of phased evolution planning and deployment suggestions for the 5G core network were proposed to provide reference for the introduction of the 5G core network in the present network.